Studi Literatur Tentang Penggunaan Software Autodesk Revit Studi Kasus Perencanaan Puskesmas Sukajadi Kota Prabumulih - Yosi Marizan (LPPM Sekolah Tinggi Teknologi Pagar Alam, 2019)
Computer Aided Design (CAD) has long been known to document architectural design work and information, replace the manual drawing method by hand and bring significant changes in project documentation. BIM (Building Information Modeling) is a paradigm shift replacing Conventional CAD. BIM is basically a digital platform for manufacturing virtual buildings. Autodesk Revit Software is a BIM (Building Information Modeling) based software that helps document projects more realistically with three-dimensional modeling. The purpose of this research in this Final Project is to design a 2-storey building using the Autodext Revit Software for modeling and drawing. The results of the study indicate the use of BIM-based applications in designing a building can simplify the design process, improve the efficiency of time, human resources and its subsequent stages. After going through an integrated process, the final model created has all the information from the architecture, structure, and output volumes automatically.